(untitled) (Journal of Dhaka National Medical College & Hospital, 2016)
Background: A frequent dilemma for obstetricians is to determine the best mode of delivery in order to optimize pregnancy outcome for both the mother and the neonate. Objective: This study was undertaken to compare demographic characteristics, parity status, antenatal care, obstetric complications and maternal outcome of all pregnancies in women who underwent caesarean section with those who had a normal vaginal delivery. Methods: This prospective study was done in the Departments of Obstetrics and Gynaecology in Dhaka National Medical College Hospital from January, 2015 to June, 2015. Women who visited for antenatal check-up and admitted for delivery in this hospital were included in the study. The subjects were divided into two groups on the basis of mode of delivery. Results: Majority of mothers who were having caesarean section and vaginal delivery falls in 20-25 yrs of age group (50.47% vs. 65.44%) . Mothers belonging to low and lower middle socioeconomic background had higher rate in vaginal birth (80.87%). While, higher rate of caesarean sections was observed among mothers of middle and high socioeconomic status compared to vaginal delivery (75.94% vs. 19.11%). Caesarean section was higher among primigravida (64.28% vs. 36.03%) and in multigravida rate of vaginal delivery was higher (63.97% vs. 35.72). Vaginal delivery was higher among mothers who on regular antenatal check-up (80.15 % vs. 72.14 %). The major indications for caesarean section in this study were fetal distress (25.71%) and previous caesarean section (24.52%). Among the mothers uneventful puerperium was present in majority cases (90% in caesarean section vs. 98.53% in vaginal delivery). Conclusion: Caesarean section is higher at Dhaka National Medical College Hospital as this hospital deals with high number of referred patients. Trend is common among primigravida, mothers of middle and high socioeconomic status having irregular antenatal check-up, fetal distress and previous caesarean section J. Dhaka National Med. Coll. Hos. 2016; 22 (01): 13-17